Bodies of Work : Civic Display and Labor in Industrial Pittsburgh - Slavishak, Edward Steven (Book collections on Project MUSE., 2008)
Cultural history of the relationship between labor and the city in turn-of-the-century Pittsburgh, which focuses on how the working-class body was used to symbolize Pittsburgh as a city of industry.